2021
DOI: 10.1002/clc.23666
|View full text |Cite
|
Sign up to set email alerts
|

First symptoms and health care pathways in hospitalized patients with acute heart failure: ICPS2 survey. A report from the Heart Failure Working Group (GICC) of the French Society of Cardiology

Abstract: Background Acute heart failure (AHF) is a common serious condition that contributes to about 5% of all emergency hospital admissions in Europe. Hypothesis To assess the type and chronology of the first AHF symptoms before hospitalization and to examine the French healthcare system pathways before, during and after hospitalization. Material and Methods A retrospective observational study including patients hospitalized for AHF Results 793 patients were included, 59.0% were men, 45.6% identified heart failure (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Critically ill patients admitted to the intensive care unit (ICU) have complex conditions and various etiologies. A study has shown that patients admitted to an ICU often have CHD (46.8%) [3]. However, few studies have assessed the prognosis of critically ill patients with CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Critically ill patients admitted to the intensive care unit (ICU) have complex conditions and various etiologies. A study has shown that patients admitted to an ICU often have CHD (46.8%) [3]. However, few studies have assessed the prognosis of critically ill patients with CHD.…”
Section: Introductionmentioning
confidence: 99%
“…According to the statistics of HF, the disease has affected 26 million cases, with the post-diagnosis 1-year and 5-year mortality rates as high as 45% and 60%, respectively [ 3 ]. The pathological mechanism of HF is complicated, with pathogenic factors involving hypertension, aging, diabetes, coronary heart disease and obesity, and the major clinical presentations of dyspnea and lower limb edema [ 4 , 5 ]. Severe HF is mainly characterized by severe symptoms induced by abnormal heart structure and function, which is common in the elderly, especially among elderly women [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our recruitment method did not allow us to access patients who are uninformed or in denial about their disease, which is certainly a big issue in heart failure. According to the ICPS2 survey administered in 2018 to nearly 800 patients hospitalized for acute heart failure at 40 centers, 1 in 3 patients was not able to name the disease [ 63 ].…”
Section: Discussionmentioning
confidence: 99%